Perancangan Sistem Informasi Pengelolaan Data Alumni Di Fakultas Hukum Universitas Sebelas Maret Surakarta - sriwijaya sriwijaya; Nuur Rochman Naafian; Kresno Ario Tri Wibowo (Politeknik Harapan Bangsa Surakarta, 2022)
The collaboration of Universitas Sebelas Maret Surakarta (UNS) with alumni has a big impact on the development of UNS. Communication between UNS and alumni must run well. Alumni data collection at the Faculty of Law UNS still uses the manual method. This method has a weakness in the alumni tracking process because alumni data is not up to date. Another problem is that there is no means of publication of activity information, this causes every activity carried out to be ineffective. Based on the description of the problem, the formulation of the problem solved in this study is